Analisa Struktur Modal dan Likuiditas Terhadap Profitabilitas Pada Perusahaan Sub Sektor Batubara - Muhamad Fahrul Raihan; Heni Hirawati (Pusat Riset dan Inovasi Nasional, 2022)
Coal mining sub-sector companies listed on the IDX from 2017 to 2021 will be the subject of this investigation, which aims to determine how capital structure and liquidity affect profitability and how they are described.A purposive sampling strategy was used to select the sample for this study.Multiple linear analysis was used to analyze the data in this study.This study found that profitability and liquidity are unaffected by the capital structure and liquidity variables.